CULTURE ÉDUCATIVE ET CONSTRUCTION DES REPRÉSENTATIONS DE L’ASPECT GRAMMATICAL EN LANGUE ÉTRANGÈRE : STRATÉGIES DES POLONOPHONES APPRENANT LE FRANÇAIS EN MILIEU FORMEL - Starościak, Katarzyna (Neofilolog, 2018)
In this paper we propose to study, through the results of the reflexive activity of verbalization, cognitive and metacognitive strategies that advanced Polish native learners in French are implementing to construct their representations of the functioning of the French grammatical aspect. The value of the grammatical aspect, expressed in French by the opposition between the passé composé tense and imparfait tense, do not completely coincide with that of the Polish aspectual opposition between perfective and imperfective verbs. Thus, the objective of this research is to analyze the impact of implicit and explicit knowledge from the source language on the construction of the operational rules concerning the grammatical aspect in French. In particular, it will be aimed to characterize the nature of this knowledge and verify how the educational culture of Polish learners affects the processing of grammatical input of the target language.